2016
DOI: 10.4174/astr.2016.90.6.328
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perioperative and short-term outcomes between robotic and conventional laparoscopic surgery for colonic cancer: a systematic review and meta-analysis

Abstract: PurposeReports from several case series have described the feasibility and safety of robotic surgery (RS) for colonic cancer. Experience is still limited in robotic colonic surgery, and a few meta-analysis has been conducted to integrate the results for colon cancer specifically. We conducted a systematic review of the available evidence comparing the surgical safety and efficacy of RS with that of conventional laparoscopic surgery (CLS) for colonic cancer.MethodsWe searched English databases (MEDLINE, Embase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Despite the concerns regarding the small number of conversions, there was no heterogeneity observed between the two studies. A meta‐analysis of comparisons of robotic versus laparoscopic approaches in colorectal cancer reported similar results …”
Section: Discussionmentioning
confidence: 79%
“…Despite the concerns regarding the small number of conversions, there was no heterogeneity observed between the two studies. A meta‐analysis of comparisons of robotic versus laparoscopic approaches in colorectal cancer reported similar results …”
Section: Discussionmentioning
confidence: 79%
“…To date, no differences have been observed in lymph nodes resected using the different approaches, although the robotic approach is favored. 19,20,21,22,23,27,28,31 As in the case of surgical wound infection, it will be interesting to keep an eye on the future impact of robotic surgery in the standardization of minimally invasive complete mesocolic excision or lateral lymph node resection in areas of the world like Europe or the United States where these techniques are not fully implemented. This might lead to an increase in the rate of harvested lymph nodes when the robotic approach is used.…”
Section: Resected Lymph Nodesmentioning
confidence: 99%
“…Two recently published studies 19,26 found that robotic surgery was associated with a significant reduction in the mortality rate, although this was not corroborated in other systematic reviews/ meta-analyses. 20,23,27,28…”
Section: Mortality (Perioperative or 30 Days After The Intervention)mentioning
confidence: 99%
“…Several studies have demonstrated the safety and efficacy of RRC for both short-and long-term outcomes [31,60,70,71] . Only one randomized controlled trial found no differences in lengths of hospital stay and the surgical complications rate between RRC and LRC groups [72] .…”
Section: Short-and Long-term Outcomesmentioning
confidence: 99%
“…Solaini et al [60] reported that conversion to open surgery was more common during LRC, with no significant differences in mortality and postoperative complication rate. Lim et al [70] concluded that the time for diet, first flatus, and first defecation, and the length of hospital stay were significantly decreased for RRC. Similarly, Rondelli et al [74] showed that the time for the first flatus was significantly shorter in RRC.…”
Section: Short-and Long-term Outcomesmentioning
confidence: 99%